Ślady żydowskie w twórczości Andrzeja Barta. Rekonesans - Słomińska, Emilia (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The article is an attempt at identifying Jewish traits in Andrzej Bart’s literary work and film documents. The Jewish elements tend to be unevenly distributed and include references to biographies of actual individuals, creating fictional figures, creating visions of real and/or fictional events enriched with symbolic dimensions. The Jewish theme is the core of the plot only in one of the novels (Fabryka muchołapek – The Flytrap Factory). The Jewish elements in Bart’s prose complement each other, or comment on each other, co-creating the writer’s narration, and are rarely part of a work’s realistic representation. The elements have many roles to play: contextual reference, attempts to present the multi-ethnic structure of Polish society, tackling the subject of the Holocaust, or antisemitism and the difficult Polish –Jewish relations. Bart tends to discuss this issue more frequently in his films, in the Złe miasto? (Evil City?) documentary series and in Radegast, shot in cooperation with Borys Lankosz.